Neutrophil to lymphocyte ratio and muscular invasion in early-stage bladder cancer: a meta-analysis. - Madonia, Massimo; Paliogiannis, Panagiotis; Solinas, Tatiana; Mangoni, Arduino Aleksander; Carru, Ciriaco; Zinellu, Angelo (European Journal of Oncology and Environmental Health, 2018)
Background: Bladder cancer is the ninth most common cancer worldwide. In its early stages, invasion of the muscle layer of the bladder is the major determinant for cystectomy. The aim of this meta-analysis was to evaluate the potential role of the neutrophil to lymphocyte ratio (NLR) in predicting muscular invasion in early-stage bladder cancer. Methods: A systematic literature search was conducted in Medline, Pubmed, Scopus and Clinicaltrials.gov databases for English language articles published in the last decade. Results: Five studies fulfilling the eligibility criteria were identified (1,612 participants, 1,217 with NMIBC and 395 with MIBC). Pooled results showed that NLR values were significantly higher in patients with MIBC (SMD: 0.45, 95% CI: 0.18-0.73; p=0.001). Conclusions: NLR is significantly higher in patients with MIBC in comparison to those with NMIBC. This simple, widely available and relatively inexpensive parameter might be useful for risk stratification in patients with early-stage BC.